PENGARUH PENGUASAAN LITERASI DIGITAL SERTA MATA KULIAH KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA STKIP PGRI LUMAJANG - Putri, Dwi Yanuarindah; Jayatri, Fidyah (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
Education today is not only about teaching and learning, the delivery of theories, and just questions and answers. From the elementary school level to college, educators and learners to students are expected to have an entrepreneurial character. This aims so that the mindset of students / students not only aspire to find jobs but are able to create their own jobs.  Likewise with the development of the era that requires educators and students to master digital technology. It is very left behind if learning activities only use board stationery and manual teaching books. Technology is growing rapidly every year. STKIP PGRI Lumajang is one of the higher education schools that implements entrepreneurship courses that have the goal that graduates can create jobs for themselves and others by utilizing digital technology. So this research aims to find out the level of mastery of digital literacy and the impact of attending entrepreneurship lectures on student entrepreneurship activities. The method in this study is quantitative research correlational approach. Data collection uses observations, questionnaires, and other supporting documents. The results showed that there is an influence between the mastery of digital literacy to the interests of entrepreneurship students, mk entrepreneurship obtained by students there is influence, and there is a simultaneous influence between the two variations on the interest variables of entrepreneurship students. This is because knowledge about the basis of entrepreneurship makes students more confident in starting a business and mastery of technology also makes it easier for students to market their business results.Keywords: Digital Literacy; Entrepreneurship Courses; Student Entrepreneurship Interests